Fields White Unto Harvest : Charles F. Parham and the Missionary Origins of Pentecostalism - Goff, James (Book collections on Project MUSE., 2015)
Table of ContentsIntroduction1The Perils of Youth2Holiness and Healing3The Gospel of the Latter Rain4The Latter Rain Spreads5The Projector of Pentecost: the Promise6The Projector of Pentecost: the Fall7Perseverance and ObscurityConclusion: Pentecost and the Legacy of Charles ParhamAppendix AAppendix BAppendix CNotesSourcesIndex.